Impact factors in innovation management. Vision from the state companies - Sosa Pérez, Natali de la Caridad; Martínez López, Yoan; Garciandía Mirón, Gregorio; Rivera López, Maria Eugenia (Cuadernos de Administración, 2024)
Innovation is becoming an increasingly important factor in the world’s economies, and therefore a timely solution to problems in companies and their contribution to the sustainable development of society. One of the first steps for its successful operation is to analyse the conditions that exist in companies and the factors that affect them. The objective of this study is to identify the impact factors on innovation management in Cuban state-owned enterprises. A Bayesian network model was constructed to analyse the behaviour of the process in several state-owned enterprises in the province of Camagüey, which are strategically important to the country. The results indicate that among the factors with the greatest impact are: leadership of innovation activities, documentation or registration of processes and their results, and the organisation’s links with other entities. It can be concluded that the tools of document, information and knowledge management, in their continuous interrelation, are factors that favour innovation management.